Post-exercise hypotension of normotensive young men through track running sessions - Pardono,Emerson (2015)
INTRODUCTION: After a single session of physical exercise the blood pressure is reduced (post-exercise hypotension, PHE) and it has been considered as a non-pharmacological mechanism to control the blood pressure. When the exercise is performed since youth it can prevent or avoid hypertension. However, it is important to consider studies with clear practical applications to optimize its reproducibility on a daily basis. OBJECTIVE: Analyze the PEH of normotensive and physically active young men after two track running sessions (maximum and submaximal). METHODS: Participated in this study 62 physically active young men (23.3 ± 4.2 years old; 75.5 ± 9.8 kg; 177.7 ± 5.5 cm; 12.0 ± 4.6% body fatF; 52.4 ± 4.0 mL.kg-1.min-1oxygen uptake), which performed a maximum laboratory exercise test for determination of maximal oxygen uptake (VO2max - aerobic power) and subsequently three randomly running sessions (maximum - T1600; submaximal - T20; control - CON), with 48h interval between themselves. Blood pressure (BP) was measured each 15min during a 60 min period after sessions. RESULTS: Both the maximum and the submaximal exercise lead to PEH. The post-exercise values of systolic blood pressure and diastolic blood pressure differed from resting value in session T20 (p<0.05). The same pattern occurred after T1600 (p<0.05), evidenced from 30th minute post-exercise. The CON did not result in PEH. The magnitude of decay for the mean BP at the 45th after maximum exercise was higher than the other sessions (p<0.05). CONCLUSION: We concluded that both maximum and submaximal exercises, performed on a track running condition, caused PEH in young normotensive and physically active men.